Dampak Kebijakan Perdagangan terhadap Pengembangan Industri Biodiesel Indonesia - Helena Juliani Purba; Bonar Marulitua Sinaga; Tanti Novianti; Reni Kustiari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2018)
EnglishIndonesian government has been promoting development of palm oil based biodiesel industry through the so-called biodiesel mandatory policy. Biodiesel is a renewable energy and low emission. Palm oil and its derivative products are the most important contributors of foreign exchange in 2017. Trade policy is required to accelerate the achievement of biodiesel industry development in Indonesia. The study is intended to analyze the impacts of trade policy (export tax by Indonesian government and import restriction by the European Union) on the development of Indonesia’s biodiesel industry. The analysis used econometrics model in the form of simultaneous equations system consisting of 27 structural and 9 identity equations, estimated using the 2SLS (Two Stage Least Squares) method. This research used annual time series data 1991–2015. The result shows that both the export tax policy by Indonesian government and palm oil import ban by European Union have positive impacts on Indonesia's biodiesel industry but do have negative impacts on the foreign exchange revenues. The negative impacts on foreign exchange revenues can be avoided by replanting policy. Whenever the European Union imposes palm oil import ban policy; then, it is suggested that Indonesian government imposes the domestic market obligation and replanting policy. IndonesianIndonesia sedang melakukan upaya pengembangan biodiesel yang bersumber dari minyak sawit dalam kebijakan mandatori biodiesel. Biodiesel adalah sumber energi terbarukan dan rendah emisi. Minyak sawit dan produk turunannya adalah penyumbang devisa negara terbesar pada tahun 2017. Kebijakan perdagangan diperlukan untuk mempercepat pencapaian pengembangan industri biodiesel Indonesia. Penelitian ini bertujuan untuk menganalisis dampak kebijakan perdagangan (pajak ekspor oleh pemerintah Indonesia dan pembatasan impor oleh Uni Eropa) terhadap pengembangan industri biodiesel Indonesia. Analisis menggunakan model ekonometrik dalam bentuk sistem persamaan simultan terdiri dari 27 persamaan struktural dan 9 persamaan identitas yang diestimasi dengan metode Two Stage Least Squares (2SLS) menggunakan data series tahunan 1990–2015. Hasil penelitian memperlihatkan bahwa kebijakan pajak ekspor oleh pemerintah Indonesia maupun larangan impor oleh Uni Eropa berdampak positif bagi perkembangan industri biodiesel Indonesia, namun berdampak negatif terhadap penerimaan devisa Indonesia. Dampak negatif terhadap penerimaan devisa dapat diatasi dengan kebijakan peremajaan kelapa sawit (replanting). Manakala Uni Eropa melakukan pelarangan impor minyak sawit, maka disarankan Pemerintah Indonesia menerapkan kebijakan domestic market obligation dan replanting.